Local Strengthening of Reinforced Concrete Structures as a Strategy for Seismic Risk Mitigation at Regional Scale. Issue 2 (May 2015) - Frascadore, Raffaele; Di Ludovico, Marco; Prota, Andrea; Verderame, Gerardo Mario; Manfredi, Gaetano; Dolce, Mauro; Cosenza, Edoardo
Recent earthquakes have clearly shown the high vulnerability of existing reinforced concrete (RC) structures. There is a crucial need to find cost-effective and efficient strategies and methods to strengthen a large number of buildings (i.e., at a regional scale) before future major earthquakes occur. A viable strategy to prevent potential damage caused by earthquakes could be to selectively upgrade local capacity of individual structural components. In the aftermath of the 6 April 2009 L'Aquila earthquake, local retrofit work based on the use of fiber polymer reinforcement (FRP) were executed to increase the seismic capacity of lightly damaged public and private buildings. According to theoretical analyses carried out on six reinforced concrete (RC) school buildings in L'Aquila, a seismic safety level of about 60% of that requested in the design of a new building can be achieved in most cases by FRP-based strengthening of exterior joints.